Louisiana's Response to Extreme Weather : A Coastal State's Adaptation Challenges and Successes - Laska, Shirley; Laska, Shirley (Cham Springer Nature, 2020)
Earth sciences; Natural disasters; Climate change; Coasts; Environmental management; Environmental law; Environmental policy; Social justice; Human rights
English
Keywords: Politics & government; Environment law; Deltas, estuaries, coastal regions; Environmental management; Climate change; Natural disasters; Earth sciences; Natural disasters; Climate change; Coasts; Environmental management; Environmental law; Environmental policy; Social justice; Human rights